Ladakh : road to heaven - Akhtar, Shamim (Delhi NISHCAM Publication, 2009)
This book is in the form of a travelogue of a solo rider. This book on Ladakh is about ones own feeling in a terrain not so easy to access yet blessed with ethereal beauty, peace and serenity.
Keywords: Civil Servant as an author; Travel; India-Ladakh